2022
DOI: 10.2147/copd.s373590
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Retrospective Claims Analysis of Oral Corticosteroid Use and Health Conditions in Newly Diagnosed Medicare FFS Patients with COPD

Abstract: We analyzed population-level administrative claims data for Medicare fee-for-service (FFS) beneficiaries to provide insights on systemic oral corticosteroid (OCS) use patterns and associated health conditions and acute events among patients newly diagnosed with chronic obstructive pulmonary disease (COPD). Background: COPD is a progressive inflammatory disease of the lungs, characterized by acute exacerbations that may lead to increased mortality. Short courses of systemic corticosteroids (SCS) are recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Recently, the American Society for Bone and Mineral Research (ASBMR) proposed guidelines for routine medical treatment following hip and spinal fractures in postmenopausal women, in which they recommend that all patients ≥65 years old with a vertebral fracture be offered anti-osteoporotic medications 13 . Unfortunately, only 7.8% of the patients in the present study were prescribed anti-osteoporotic medications, which aligns with previous reports of osteoporosis treatment rates following fragility fractures 2 . Barton et al found a 7% rate of treatment with antiresorptive medications following a vertebral OCF in their retrospective review of 2,933 patients 3 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, the American Society for Bone and Mineral Research (ASBMR) proposed guidelines for routine medical treatment following hip and spinal fractures in postmenopausal women, in which they recommend that all patients ≥65 years old with a vertebral fracture be offered anti-osteoporotic medications 13 . Unfortunately, only 7.8% of the patients in the present study were prescribed anti-osteoporotic medications, which aligns with previous reports of osteoporosis treatment rates following fragility fractures 2 . Barton et al found a 7% rate of treatment with antiresorptive medications following a vertebral OCF in their retrospective review of 2,933 patients 3 .…”
Section: Discussionsupporting
confidence: 90%
“…They comprise 27% of all osteoporotic fractures and are the most common osteoporotic fracture among the aging population 1 . In 2015, Medicare spent $658 million on vertebral OCFs, which had an incidence of 102.1 per 10,000 Medicare beneficiaries and a 1-year mortality rate of 21% 2 . The risk of secondary fracture within 12 months of the index event was 15% among these patients 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Another study using Medicare claims data from 2013 to 2019 found that 36% of patients newly diagnosed with COPD received OCS in the 48 months following diagnosis, lasting longer than 5–7 days for 38% of episodes. 11 …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Short courses of oral corticosteroids at a daily dose of 40 mg prednisolone equivalent for 5-7 days are routine in the treatment of acute exacerbations. However, Bazell et al 21 have shown that treatment with daily doses of over 1000 mg prednisolone equivalent was associated with a higher incidence of events that may be OCS-related, including CVD and heart failure. While we lack data on the total accumulated OCS doses, it is possible that patients in our study receiving large doses of steroids to treat acute COPD could have contributed to our results.…”
mentioning
confidence: 99%